Re-evaluation of the psychometric properties of ATE following changes in euthanasia regulations in Spain - Daniel Lerma-García; María Laura Parra-Fernandez; Cristina Romero-Blanco; Sandra Martínez-Rodriguez; María Dolores Onieva-Zafra (PLoS ONE, 2025)
Understanding healthcare professionals’ attitudes toward euthanasia, especially within teams assisting patients who request it, is essential for providing appropriate support throughout the process. The objectives of this study were to re-adapt and validate the Attitude Towards Euthanasia Scale for the Spanish context, to examine its dimensional structure, and to estimate its reliability, particularly in light of the 2021 regulation of euthanasia in Spain. A cross-sectional study was conducted with a non-probabilistic sample of 778 healthcare professionals from the Balearic Health Service. Data collection involved a self-reported sociodemographic questionnaire and the Attitude Towards Euthanasia Scale. The scale’s psychometric properties were assessed through reliability and validity tests, including confirmatory factor analysis. The Attitude Towards Euthanasia Scale demonstrated strong reliability, with a Cronbach’s alpha of α = 0.889 and item homogeneity ranging from 0.66 to 0.78. Factor loadings were reported for four models, including a unidimensional model and models with two, three, and four factors. The two-factor model explained 64.51% of the variance, with a Kaiser-Meyer-Olkin (KMO) value of 0.873. Fit indices indicated good model fit: root mean square residual = 0.040, goodness-of-fit index = 0.960, adjusted goodness-of-fit index = 0.927, and root mean square error of approximation = 0.069. After performing a Parallel Analysis, two loading factor were found. The adapted version of the Attitude Towards Euthanasia Scale, aligned with the current societal and legislative context, is a valid and reliable tool for assessing healthcare professionals’ attitudes toward euthanasia, with psychometric properties consistent with the original version.